THE EFFECTIVENESS BETWEEN DISCOVERY LEARNING AND WORD WALL METHODS IN IMPROVING VOCABULARY AT SEVENTH GRADE STUDENTS - Junizar, Fahmi; Sudiyono, Sudiyono (IKIP Siliwangi, 2020)
Some of the teacher is having a problem when using discovery learning as a method to improve the vocabulary of a student. Based on the objective of this research, the writer conduct wordwall method on SMP mutiara 1 Bandung that will help on improving student vocabulary, and hopefully it can be applied simultaneously to increase interest in learning especially in English course in SMP Mutiara 1 Bandung. Based on the results of research that has been done by the writer, there are very helpful results in developing the method of Word Wall as a teaching material capable of improving the quality of learning and also can improve students vocabulary. From the test results of normality and homogeneity that the data used is homogeneous and distributed normally, so that the process of the research can be continued as it should be. Keywords: Vocabulary, Discovery Learning, Wordwall